Method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid
By adjusting the pH value of the electroless nickel plating waste liquid and adding calcium chloride precipitation, combined with the reduction reaction of hydrazine hydrate and the purification treatment of adsorption purifier, the problem of recycling and utilization of nickel and phosphorus resources in the waste liquid is successfully solved, and efficient and environmentally friendly resource recycling and wastewater treatment are achieved.
Patent Information
- Application Number
- CN202510356756.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
It is difficult to recycle nickel and phosphorus resources in electroless nickel plating waste liquid, resulting in waste of resources and environmental pollution.
Precipitation is performed by adjusting the pH value of the waste liquid and adding calcium chloride, followed by reducing nickel ions using hydrazine hydrate, and finally the prepared adsorption purifier is used to further purify and discharge the waste liquid.
It realizes high-purity recycling and resource utilization of nickel and phosphorus, reduces treatment costs, improves the utilization rate of waste liquid, and enables wastewater to meet dischargeable standards, which has environmental protection and economic advantages.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste liquid treatment, and in particular to a method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid. Background Art
[0002] Electroplating is a common process in the national processing and manufacturing industry, and is widely used in the fields of machinery, electronics, aerospace, etc. Chemical nickel plating is an important branch of the electroplating industry. Due to its excellent corrosion resistance, wear resistance, weldability and uniform thickness, it has been widely used around the world.
[0003] The rapid development of the chemical nickel plating industry has also brought about the problem of a large amount of chemical nickel plating waste liquid that needs to be treated. Chemical nickel plating waste liquid contains 2-8g / L nickel ions, about 100-200g / L phosphite, >80g / L sodium sulfate, 10-20g / L ammonia nitrogen, chemical oxygen demand (COD) >200g / L and trace amounts of other metal impurities. On the one hand, the waste plating solution contains available resources, such as nickel, phosphorus, nitrogen, etc.; on the other hand, nickel is also an important source of pollution, and direct discharge pollutes the environment. Therefore, if the chemical nickel plating process is to be applied to industrial production, waste liquid treatment is an urgent problem that must be solved. According to the current electroplating pollutant emission standards in my country (GB21900-2008), the concentration of nickel allowed to be discharged is only 0.1mg / L, and the concentration of total phosphorus allowed to be discharged is 0.5mg / L.
[0004] Nickel is a scarce and expensive metal resource. The price of nickel in the international market has remained high in recent years. In 2020, the price of nickel metal rose to 140,000 yuan / ton. At the same time, phosphorus resources are also one of the scarce resources in my country. The Ministry of Land and Resources of China has listed phosphate resources as one of the important minerals that cannot meet the needs of national economic development after 2010. In recent years, a large number of scholars are studying how to extract increasingly valuable phosphorus resources from sludge generated by domestic sewage treatment plants. If the nickel and phosphorus in the chemical nickel plating waste liquid are not recycled and discharged at will, it will inevitably cause a waste of such scarce and valuable resources.
[0005] At the same time, phosphorus is also one of the scarce resources in my country. The Ministry of Land and Resources of China has listed phosphate resources as one of the important minerals that cannot meet the needs of national economic development after 2010. In recent years, a large number of scholars are studying how to extract increasingly valuable phosphorus resources from sludge produced by domestic sewage treatment plants. If the phosphorus in chemical nickel plating wastewater is not recycled and discharged at will, it will inevitably cause a waste of such scarce and valuable resources.
[0006] At present, the main treatment methods for chemical nickel plating waste liquid include chemical precipitation method, Fenton method, etc. These methods often require the addition of a large amount of sewage treatment agents, which is costly. At the same time, it is difficult to recover the phosphorus resources in the waste liquid, resulting in waste of resources, generating a large amount of sludge, and easily causing secondary pollution. Summary of the invention
[0007] The purpose of the present invention is to propose a method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid. A simple and environmentally friendly method is used to effectively separate nickel and phosphorus in chemical nickel plating waste liquid, and relatively high-purity phosphorus and nickel by-products can be obtained, which are further utilized as resources and their economic value is improved. After further adsorption and purification, they can be directly discharged, which is more cost-effective, green and environmentally friendly, and has broad application prospects.
[0008] The technical solution of the present invention is achieved in this way: The present invention provides a method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid, comprising the following steps: (1) adjusting the pH value of the chemical nickel plating waste liquid, then adding calcium chloride to the chemical nickel plating waste liquid, stirring the reaction to precipitate, centrifuging, collecting the precipitate, and precipitating into a substance containing calcium phosphate and calcium phosphite; (2) adding sodium hydroxide to the supernatant in step (1) to adjust the pH value, centrifuging, separating the solid, adding hydrazine hydrate to the supernatant, stirring to react, and stopping adding hydrazine hydrate after no more bubbles are generated in the reaction solution, continuing to stir the reaction, standing to precipitate, centrifuging, and collecting the precipitate, which is a substance containing metallic nickel; (3) introducing carbon dioxide into the supernatant in step (2) to precipitate, adding an adsorption purifier to the filtrate, stirring and adsorbing, separating the adsorption purifier with a magnet, and discharging the filtrate after it meets the standards; The adsorption purifier is a material with magnetic ferroferric oxide as the core, loaded with doped TiO2 / ZnO, and then subjected to hydrogenation treatment, carbon nanotubes are deposited on the surface, and after being modified with polydopamine, the adsorption purifier is reacted with zirconium tetrachloride and 2-aminoterephthalic acid to obtain the adsorption purifier.
[0009] As a further improvement of the present invention, the amount of calcium chloride added to the chemical nickel plating waste liquid in step (1) is 12-15g of calcium chloride per 100mL of chemical nickel plating waste liquid, the stirring reaction precipitation time is 1-2h, and the pH value of the chemical nickel plating waste liquid is adjusted to 6.9-7.1.
[0010] As a further improvement of the present invention, in step (2), the pH value is adjusted to 10-11, the stirring reaction time is 0.5-1h, and the stirring reaction time is continued to be 0.5-1h.
[0011] As a further improvement of the present invention, the amount of the adsorption purifier added in step (3) is 3-5wt%, the stirring adsorption time is 10-20min, the ventilation rate of the carbon dioxide is 10-100mL / min, and the preparation method of the adsorption purifier is as follows: S1. Preparation of magnetic ferroferric oxide: under the protection of inert gas, ferric chloride and ferrous chloride are added to water, ammonia is added dropwise to adjust the pH value of the solution, heating and stirring the reaction, centrifuging, washing, ball milling, drying, and calcining to obtain magnetic ferroferric oxide; S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: dissolve zinc acetate and cupric chloride in water, add diethylene glycol, and stir to form solution A; mix tetrabutyl titanate, thiourea, acetic acid and ethanol to obtain solution B; mix solution A and solution B, add magnetic ferroferric oxide, heat and stir to react, centrifuge, wash, ball mill, dry, and calcine to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: The air was replaced by introducing an inert gas into the doped TiO2 / ZnO@magnetic ferroferric oxide composite, and then hydrogen was introduced, heated, the introduction of hydrogen was stopped, and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: dissolving ferrocene in xylene to obtain a solution, introducing an inert gas into the black doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, turning off the inert gas, introducing hydrogen, heating, adding the solution dropwise, then stopping heating and introducing hydrogen, cooling to room temperature, and obtaining a carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S5. Polydopamine modification: adding the prepared carbon nanotube deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite to water, adding dopamine hydrochloride and a catalyst, heating and stirring the reaction, separating with a magnet, washing, and drying to obtain a modified product; S6. Preparation of adsorption purifier: Add the modified substance, zirconium tetrachloride and 2-aminoterephthalic acid into N,N-dimethylformamide, stir and mix evenly, add acetic acid dropwise, perform hydrothermal reaction, separate by magnet, wash and dry to obtain adsorption purifier.
[0012] As a further improvement of the present invention, the mass ratio of ferric chloride to ferrous chloride in step S1 is 3.24:1.26, the pH value of the adjusted solution is 10-11, the temperature of the heated and stirred reaction is 75-85°C, the time is 4-6h, and the calcination temperature is 400-600°C, and the time is 1-3h.
[0013] As a further improvement of the present invention, the mass ratio of zinc acetate, cupric chloride, diethylene glycol, tetrabutyl titanate, thiourea, acetic acid and magnetic ferrosoferric oxide in step S2 is 7-10:0.2-0.4:3-5:12-15:1-2:4-6:6-8, the temperature of the heating and stirring reaction is 65-75°C, the time is 1-2h, and the calcination temperature is 500-600°C, and the time is 1-3h.
[0014] As a further improvement of the present invention, in step S3, hydrogen is introduced until the hydrogen pressure reaches 20-30 bar, and the temperature of the heating treatment is 180-220° C. for 4-6 days.
[0015] As a further improvement of the present invention, in step S4, the mass ratio of ferrocene to xylene is 1-2:100, the ventilation rate of hydrogen is 50-100 mL / min, and the heating temperature is 800-900°C.
[0016] As a further improvement of the present invention, the mass ratio of the carbon nanotube deposited black doped TiO2 / ZnO@magnetic ferroferric oxide complex, dopamine hydrochloride and catalyst in step S5 is 10:3-5:0.5-1, the catalyst has a pH of 8.5-9.5 Tris-HCl solution, the temperature of the heated and stirred reaction is 45-55°C, and the time is 3-5h.
[0017] As a further improvement of the present invention, in step S6, the mass ratio of the modified substance, zirconium tetrachloride, 2-aminoterephthalic acid and acetic acid is 10:4-5:3-4:2-4, the temperature of the hydrothermal reaction is 120-140° C., and the time is 20-24 h.
[0018] The present invention has the following beneficial effects: In the present invention, soluble calcium salt, calcium chloride, is used as a precipitant to react with excess phosphate and phosphite in waste liquid to form precipitates. In order to prevent the pH value from being too high to cause calcium hydroxide precipitates to be generated, and too low to cause the generated precipitates to dissolve and affect the removal effect of phosphorus in the waste liquid, the experiment is first conducted under the condition that the waste liquid value is about 7, and an excessive amount is added to ensure that phosphorus can be fully precipitated. The obtained material containing calcium phosphate and calcium phosphite can be further utilized as a resource after further purification, which greatly improves the utilization rate of the waste liquid and improves its economic value. At the same time, it also avoids the participation of phosphorus in the reaction during the subsequent hydrazine hydrate reaction.
[0019] Subsequently, the present invention adds hydrazine hydrate as a reducing agent, and the chemical equation is as follows: 2Ni 2+ + N2H4 + 4OH - = 2Ni↓ + N2↑ + 4H2O Using hydrazine hydrate to reduce excess Ni in wastewater 2+ , nickel salt is reduced with hydrazine hydrate in aqueous phase to obtain nickel nanoparticles with uniform particle size. The products are nitrogen and water, which will introduce other impurities into the waste liquid. The obtained substance containing metallic nickel can be purified to obtain Ni metal with higher purity.
[0020] After separating the main pollutants phosphorus and nickel in the present invention, carbon dioxide is introduced to remove excess calcium ions and other large amounts of metal ions. The present invention further adds an adsorption purifier to further treat the waste liquid, which can adsorb other small amounts of impurities such as heavy metal ions, organic matter, and ammonia nitrogen impurities, so that the wastewater can meet the discharge standards, which is beneficial to environmental protection.
[0021] The adsorption purifier prepared by the present invention uses magnetic ferroferric oxide as a core, which is conducive to the magnetic separation of the adsorption purifier, thereby making it easy to operate and simplifying the operation steps. A doped TiO2 / ZnO composite is deposited on the surface of the magnetic ferroferric oxide, and metallic copper, non-metallic sulfur and nitrogen are used as dopants, so that the band gap structure of titanium dioxide and zinc oxide can be adjusted to make them more sensitive to visible light, improve their response ability to visible light, introduce new energy levels, narrow the band gap, and thus improve the visible light absorption capacity, so that the adsorption purifier can effectively use visible light to photocatalytically degrade organic impurities in water, and achieve a purification effect.
[0022] The prepared doped TiO2 / ZnO@magnetic ferroferric oxide composite was hydrogenated to transform it into black, with a significantly reduced band gap, capable of absorbing visible light, infrared light, and ultraviolet light. 3+ Self-doping defects enhance the separation efficiency of photogenerated charges, thereby improving the photocatalytic performance and the ability to purify pollutants.
[0023] Further deposition of carbon nanotubes on the surface of the prepared black-doped TiO2 / ZnO@magnetic ferroferric oxide composite to construct a heterostructure can effectively inhibit the recombination of photogenerated carriers and improve the photocatalytic efficiency. At the same time, it greatly increases the specific surface area of the composite, which is helpful for the adsorption and fixation of pollutants.
[0024] The surface of the prepared carbon nanotube deposited black doped TiO2 / ZnO@magnetic ferroferric oxide complex is modified with polydopamine. The obtained modified product, on the one hand, contains rich active groups such as amino groups, which can fix metal ions by forming complex bonds, fix organic matter by forming hydrogen bonds, and can adsorb zirconium ions, thereby generating a UiO-66-NH2 structure on its surface. The amino straw strengthens the fixation of heavy metal ions and organic matter, and the large specific surface area greatly improves the adsorption effect of pollutants.
[0025] The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid of the present invention adopts a simple and environmentally friendly method to effectively separate nickel and phosphorus in chemical nickel plating waste liquid, and can obtain phosphorus and nickel by-products with relatively high purity, which are further utilized as resources, thereby improving their economic value. After further adsorption and purification, they can be directly discharged, which is more cost-effective, green and environmentally friendly, and has broad application prospects. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Preparation Example 1 Preparation of adsorption purifier Here’s how: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g of ferric chloride and 1.26 g of ferrous chloride were added to 150 mL of water, and ammonia was added dropwise to adjust the pH value of the solution to 10. The solution was heated to 75 ° C, stirred for 4 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 400 ° C for 1 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 7g zinc acetate and 0.2g copper chloride were dissolved in 200mL water, 3g diethylene glycol was added, and the mixture was stirred to form solution A; 12g tetrabutyl titanate, 1g thiourea, 4g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 6g magnetic ferroferric oxide was added, heated to 65°C, stirred for reaction for 1h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 500°C for 1h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, and then hydrogen was introduced to a hydrogen pressure of 20 bar, heated to 180°C, treated for 4 days, and then the introduction of hydrogen was stopped and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: 0.05 g of ferrocene was dissolved in 5 g of xylene to obtain a solution, nitrogen was introduced into the black doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, the nitrogen was turned off, hydrogen was introduced at a flow rate of 50 mL / min, the mixture was heated to 800°C, the solution was added dropwise, and the mixture was kept for 30 min, then the heating and the introduction of hydrogen were stopped, and the mixture was cooled to room temperature to obtain a carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S5. Polydopamine modification: 10 g of carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite was added to 150 mL of water, 3 g of dopamine hydrochloride and 0.5 g of catalyst were added, heated to 45 ° C, stirred for 3 h, separated by a magnet, washed, and dried to obtain a modified product; The catalyst has a pH of 8.5 in a Tris-HCl solution; S6. Preparation of adsorption purifier: 10 g of the modified product, 4 g of zirconium tetrachloride and 3 g of 2-aminoterephthalic acid were added to 500 mL of N,N-dimethylformamide, stirred for 15 min, 2 g of acetic acid was added dropwise, hydrothermally reacted at 120° C. for 20 h, separated by a magnet, washed and dried to obtain an adsorption purifier.
[0028] Preparation Example 2 Preparation of adsorption purifier Here’s how: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g ferric chloride and 1.26 g ferrous chloride were added to 150 mL water, and ammonia was added dropwise to adjust the pH value of the solution to 11. The solution was heated to 85 ° C, stirred for 6 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 600 ° C for 3 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 10g zinc acetate and 0.4g copper chloride were dissolved in 200mL water, 5g diethylene glycol was added, and the mixture was stirred to form solution A; 15g tetrabutyl titanate, 2g thiourea, 6g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 8g magnetic ferroferric oxide was added, heated to 75°C, stirred and reacted for 2h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 600°C for 3h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, and then hydrogen was introduced to a hydrogen pressure of 30 bar, heated to 220°C, treated for 6 days, and the introduction of hydrogen was stopped, and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: 0.1 g of ferrocene was dissolved in 5 g of xylene to obtain a solution, nitrogen was introduced into the black doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, the nitrogen was turned off, hydrogen was introduced at a flow rate of 100 mL / min, the solution was added dropwise to heat to 900°C, and the mixture was kept for 40 min, then the heating and the introduction of hydrogen were stopped, and the mixture was cooled to room temperature to obtain a carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S5. Polydopamine modification: 10 g of carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite was added to 150 mL of water, 5 g of dopamine hydrochloride and 1 g of catalyst were added, heated to 55 ° C, stirred for 5 h, separated by a magnet, washed, and dried to obtain a modified product; The catalyst has a pH of 9.5 in a Tris-HCl solution; S6. Preparation of adsorption purifier: 10 g of the modified product, 5 g of zirconium tetrachloride and 4 g of 2-aminoterephthalic acid were added to 500 mL of N,N-dimethylformamide, stirred for 15 min, 4 g of acetic acid was added dropwise, hydrothermally reacted at 140° C. for 24 h, separated by a magnet, washed and dried to obtain an adsorption purifier.
[0029] Preparation Example 3 Preparation of adsorption purifier Here’s how: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g ferric chloride and 1.26 g ferrous chloride were added to 150 mL water, and ammonia was added dropwise to adjust the pH value of the solution to 10.5. The solution was heated to 80 ° C, stirred for 5 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 500 ° C for 2 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate and 0.3g copper chloride were dissolved in 200mL water, 4g diethylene glycol was added, and the mixture was stirred to form solution A; 13.5g tetrabutyl titanate, 1.5g thiourea, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70°C, stirred for reaction for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550°C for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, and then hydrogen was introduced to a hydrogen pressure of 25 bar, heated to 200°C, treated for 5 days, and then the introduction of hydrogen was stopped and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: 0.07 g of ferrocene was dissolved in 5 g of xylene to obtain a solution, nitrogen was introduced into the black doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, the nitrogen was turned off, hydrogen was introduced at a flow rate of 70 mL / min, the solution was added dropwise to heat to 850°C, the temperature was kept at 35 min, and then the heating and hydrogen introduction were stopped, and the mixture was cooled to room temperature to obtain a carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S5. Polydopamine modification: 10 g of carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite was added to 150 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 50 ° C, stirred for 4 h, separated by a magnet, washed, and dried to obtain a modified product; A Tris-HCl solution of the catalyst with a pH of 9; S6. Preparation of adsorption purifier: 10 g of the modified product, 4.5 g of zirconium tetrachloride and 3.5 g of 2-aminoterephthalic acid were added to 500 mL of N,N-dimethylformamide, stirred for 15 min, 3 g of acetic acid was added dropwise, hydrothermally reacted at 130° C. for 22 h, separated by a magnet, washed and dried to obtain an adsorption purifier.
[0030] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that copper chloride is not added in step S2.
[0031] The details are as follows: S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate was dissolved in 200mL water, 4g diethylene glycol was added and stirred to form solution A; 13.5g tetrabutyl titanate, 1.8g thiourea, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70℃, stirred for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550℃ for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite.
[0032] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that thiourea is not added in step S2.
[0033] The details are as follows: S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate and 1.8g cupric chloride were dissolved in 200mL water, 4g diethylene glycol was added and stirred to form solution A; 13.5g tetrabutyl titanate, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70℃, stirred for 1.5h, centrifuged, washed, ball milled for 1h, dried, and calcined at 550℃ for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite.
[0034] Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that copper chloride and thiourea are not added in step S2.
[0035] The details are as follows: S2. Preparation of TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate was dissolved in 200mL water, 4g diethylene glycol was added and stirred to form solution A; 13.5g tetrabutyl titanate, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70℃, stirred for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550℃ for 2h to obtain TiO2 / ZnO@magnetic ferroferric oxide composite.
[0036] Comparative Preparation Example 4 Compared with Preparation Example 3, the difference is that step S3 is not performed.
[0037] The details are as follows: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g ferric chloride and 1.26 g ferrous chloride were added to 150 mL water, and ammonia was added dropwise to adjust the pH value of the solution to 10.5. The solution was heated to 80 ° C, stirred for 5 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 500 ° C for 2 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate and 0.3g copper chloride were dissolved in 200mL water, 4g diethylene glycol was added, and the mixture was stirred to form solution A; 13.5g tetrabutyl titanate, 1.5g thiourea, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70°C, stirred for reaction for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550°C for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Deposition of carbon nanotubes: 0.07 g of ferrocene was dissolved in 5 g of xylene to obtain a solution, nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, the nitrogen was turned off, hydrogen was introduced at a flow rate of 70 mL / min, the temperature was heated to 850°C, the solution was added dropwise, and the temperature was maintained for 35 min, then the heating and the introduction of hydrogen were stopped, and the mixture was cooled to room temperature to obtain a doped TiO2 / ZnO@magnetic ferroferric oxide composite with carbon nanotube deposition; S4. Polydopamine modification: 10 g of carbon nanotube deposited doped TiO2 / ZnO@magnetic ferroferric oxide composite was added to 150 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 50 ° C, stirred for 4 h, separated by a magnet, washed, and dried to obtain a modified product; A Tris-HCl solution of the catalyst with a pH of 9; S5. Preparation of adsorption purifier: 10 g of the modified product, 4.5 g of zirconium tetrachloride and 3.5 g of 2-aminoterephthalic acid were added to 500 mL of N,N-dimethylformamide, stirred for 15 min, 3 g of acetic acid was added dropwise, hydrothermally reacted at 130° C. for 22 h, separated by magnet, washed and dried to obtain an adsorption purifier.
[0038] Comparative Preparation Example 5 Compared with Preparation Example 3, the difference is that step S4 is not performed.
[0039] The details are as follows: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g ferric chloride and 1.26 g ferrous chloride were added to 150 mL water, and ammonia was added dropwise to adjust the pH value of the solution to 10.5. The solution was heated to 80 ° C, stirred for 5 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 500 ° C for 2 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate and 0.3g copper chloride were dissolved in 200mL water, 4g diethylene glycol was added, and the mixture was stirred to form solution A; 13.5g tetrabutyl titanate, 1.5g thiourea, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70°C, stirred for reaction for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550°C for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, and then hydrogen was introduced to a hydrogen pressure of 25 bar, heated to 200°C, treated for 5 days, and then the introduction of hydrogen was stopped and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Polydopamine modification: 10 g of black doped TiO2 / ZnO@magnetic ferroferric oxide composite was added to 150 mL of water, 4 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 50 ° C, stirred for 4 h, separated by magnet, washed, and dried to obtain a modified product; A Tris-HCl solution of the catalyst with a pH of 9; S5. Preparation of adsorption purifier: 10 g of the modified product, 4.5 g of zirconium tetrachloride and 3.5 g of 2-aminoterephthalic acid were added to 500 mL of N,N-dimethylformamide, stirred for 15 min, 3 g of acetic acid was added dropwise, hydrothermally reacted at 130° C. for 22 h, separated by magnet, washed and dried to obtain an adsorption purifier.
[0040] Comparative Preparation Example 6 Compared with Preparation Example 3, the difference is that step S6 is not performed.
[0041] The details are as follows: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g ferric chloride and 1.26 g ferrous chloride were added to 150 mL water, and ammonia was added dropwise to adjust the pH value of the solution to 10.5. The solution was heated to 80 ° C, stirred for 5 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 500 ° C for 2 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate and 0.3g copper chloride were dissolved in 200mL water, 4g diethylene glycol was added, and the mixture was stirred to form solution A; 13.5g tetrabutyl titanate, 1.5g thiourea, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70°C, stirred for reaction for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550°C for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, and then hydrogen was introduced to a hydrogen pressure of 25 bar, heated to 200°C, treated for 5 days, and then the introduction of hydrogen was stopped and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: 0.07 g of ferrocene was dissolved in 5 g of xylene to obtain a solution, nitrogen was introduced into the black doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, the nitrogen was turned off, hydrogen was introduced at a flow rate of 70 mL / min, the solution was added dropwise to heat to 850°C, the temperature was kept at 35 min, and then the heating and hydrogen introduction were stopped, and the mixture was cooled to room temperature to obtain a carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S5. Polydopamine modification: 10g of carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite was added to 150mL of water, 4g of dopamine hydrochloride and 0.7g of catalyst were added, heated to 50°C, stirred for 4h, separated by a magnet, washed, and dried to obtain a modified product, which is an adsorption purifier; The catalyst is a Tris-HCl solution with a pH of 9.
[0042] Comparative Preparation Example 7 Compared with Preparation Example 3, the difference is that steps S5 and S6 are not performed.
[0043] The details are as follows: S1. Preparation of magnetic ferroferric oxide: Under nitrogen protection, 3.24 g ferric chloride and 1.26 g ferrous chloride were added to 150 mL water, and ammonia was added dropwise to adjust the pH value of the solution to 10.5. The solution was heated to 80 ° C, stirred for 5 h, centrifuged, washed, ball milled for 1 h, dried, and calcined at 500 ° C for 2 h to obtain magnetic ferroferric oxide. S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: 8.5g zinc acetate and 0.3g copper chloride were dissolved in 200mL water, 4g diethylene glycol was added, and the mixture was stirred to form solution A; 13.5g tetrabutyl titanate, 1.5g thiourea, 5g acetic acid and 100mL ethanol were stirred and mixed for 10min to obtain solution B; after mixing solution A and solution B, 7g magnetic ferroferric oxide was added, heated to 70°C, stirred for reaction for 1.5h, centrifuged, washed, ball-milled for 1h, dried, and calcined at 550°C for 2h to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: nitrogen was introduced into the doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, and then hydrogen was introduced to a hydrogen pressure of 25 bar, heated to 200°C, treated for 5 days, and then the introduction of hydrogen was stopped and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: Dissolve 0.07g of ferrocene in 5g of xylene to obtain a solution, introduce nitrogen into the black doped TiO2 / ZnO@magnetic ferroferric oxide complex to replace the air, turn off the nitrogen, introduce hydrogen at a flow rate of 70mL / min, heat to 850℃, add the solution dropwise, maintain for 35min, then stop heating and introducing hydrogen, cool to room temperature, and obtain carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide complex, which is the adsorption purifier.
[0044] Test Example 1 Determination of specific surface area The specific surface areas of the adsorption purifiers prepared in Preparation Examples 1-3 and Comparative Preparation Examples 1-7 were measured using a 3-FLEX 3500 multi-station high-throughput gas adsorption instrument. The results are shown in Table 1.
[0045] Table 1
[0046] It can be seen from the above table that the adsorption purifiers prepared in Preparation Examples 1-3 of the present invention have a large specific surface area.
[0047] Test Example 2 Configuration 10 -4mol / L cephalexin solution was used as antibiotic contaminated sewage. 0.1mol / L hydrochloric acid and 0.01mol / L sodium hydroxide were used to adjust the sewage to pH=7. 100ml of cephalexin solution was taken, and 5mg of the adsorption purifier prepared in Preparation Example 1-3 and Comparative Preparation Example 1-7 were added respectively. Under visible light irradiation, the adsorption purifier was stirred at 500r / min for 10min, and the adsorption purifier was separated by magnet. The clear liquid was collected and centrifuged at 10000rpm for 10min, and the supernatant was collected. The absorption peak of the solution at 262nm was detected by ultraviolet-visible spectrophotometer, and the removal effect of the adsorption purifier on cephalexin was calculated. The results are shown in Table 2.
[0048] Table 2
[0049] It can be seen from the above table that the adsorption purifiers prepared in Preparation Examples 1-3 of the present invention have good visible light catalytic degradation effects on antibiotic organic matter.
[0050] Example 1
[0051] This embodiment provides a method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid, comprising the following steps: (1) adjusting the pH value of the chemical nickel plating waste liquid to 6.9, then adding calcium chloride to the chemical nickel plating waste liquid, the amount of calcium chloride added is 12 g of calcium chloride per 100 mL of the chemical nickel plating waste liquid, stirring the reaction to precipitate for 1 hour, centrifuging, collecting the precipitate, and the precipitate is a substance containing calcium phosphate and calcium phosphite; (2) sodium hydroxide was added to the supernatant in step (1) to adjust the pH value to 10, centrifuged, separated the solid, added hydrazine hydrate to the supernatant, stirred and reacted for 0.5 h, and when no more bubbles were generated in the reaction solution, the addition of hydrazine hydrate was stopped, and the reaction was continued with stirring for 0.5 h, allowed to stand and precipitate, centrifuged, and the precipitate was collected, which was a substance containing metallic nickel; (3) Carbon dioxide was introduced into the supernatant in step (2) at a flow rate of 50 mL / min for 1 h. The mixture was allowed to settle for 1 h. The adsorption purifier prepared in Preparation Example 1 was added to the filtrate at an amount of 3 wt %. The mixture was stirred and adsorbed for 10 min. The adsorption purifier was separated by a magnet. After the filtrate met the standards, it was discharged.
[0052] Example 2
[0053] This embodiment provides a method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid, comprising the following steps: (1) adjusting the pH value of the chemical nickel plating waste liquid to 7.1, then adding calcium chloride to the chemical nickel plating waste liquid, the amount of calcium chloride added is 15g of calcium chloride per 100mL of the chemical nickel plating waste liquid, stirring the reaction for 2h, centrifuging, collecting the precipitate, and the precipitate is a substance containing calcium phosphate and calcium phosphite; (2) adding sodium hydroxide to the supernatant in step (1) to adjust the pH value to 11, centrifuging, separating the solid, adding hydrazine hydrate to the supernatant, stirring and reacting for 1 hour, and stopping adding hydrazine hydrate after no more bubbles are generated in the reaction solution, continuing to stir and react for 1 hour, allowing to stand and precipitate, centrifuging, and collecting the precipitate, which is a substance containing metallic nickel; (3) Carbon dioxide was introduced into the supernatant in step (2) at a flow rate of 100 mL / min for 1 h. The mixture was allowed to settle for 1 h. The adsorption purifier prepared in Preparation Example 2 was added to the filtrate at a concentration of 5 wt%. The mixture was stirred and adsorbed for 20 min. The adsorption purifier was separated by a magnet. After the filtrate met the standards, it was discharged.
[0054] Example 3
[0055] This embodiment provides a method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid, comprising the following steps: (1) adjusting the pH value of the chemical nickel plating waste liquid to 7, then adding calcium chloride to the chemical nickel plating waste liquid, the amount of calcium chloride added is 13 g of calcium chloride per 100 mL of the chemical nickel plating waste liquid, stirring the reaction to precipitate for 1.5 hours, centrifuging, collecting the precipitate, and the precipitate is a substance containing calcium phosphate and calcium phosphite; (2) adding sodium hydroxide to the supernatant in step (1) to adjust the pH value to 10.5, centrifuging, separating the solid, adding hydrazine hydrate to the supernatant, stirring and reacting for 1 hour, and stopping adding hydrazine hydrate after no more bubbles are generated in the reaction solution, continuing to stir and react for 1 hour, allowing to stand and precipitate, centrifuging, and collecting the precipitate, which is a substance containing metallic nickel; (3) Carbon dioxide was introduced into the supernatant in step (2) at a ventilation rate of 75 mL / min for 1 h. The mixture was allowed to settle for 1 h. The adsorption purifier prepared in Preparation Example 3 was added to the filtrate at a dosage of 4 wt%. The mixture was stirred and adsorbed for 15 min. The adsorption purifier was separated by a magnet. After the filtrate met the standards, it was discharged.
[0056] Comparative Example 1 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1.
[0057] Comparative Example 2 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1.
[0058] Comparative Example 3 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1.
[0059] Comparative Example 4 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1.
[0060] Comparative Example 5 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1.
[0061] Comparative Example 6 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1 Comparative Example 7 Compared with Example 3, the difference is that the adsorption purifier is prepared by Comparative Preparation Example 1.
[0062] Comparative Example 8 Compared with Example 3, the difference is that step (1) is not performed.
[0063] The details are as follows: (1) sodium hydroxide is added to the chemical nickel plating waste liquid to adjust the pH value to 10.5, centrifuged, separated the solid, added hydrazine hydrate to the supernatant, stirred and reacted for 1 hour, and when no bubbles are generated in the reaction liquid, the addition of hydrazine hydrate is stopped, and the stirring reaction is continued for 1 hour, allowed to stand and precipitate, centrifuged, and the precipitate is collected, which is a substance containing metallic nickel; (2) Carbon dioxide was introduced into the supernatant of step (1) at a ventilation rate of 75 mL / min for 1 h. The mixture was allowed to settle for 1 h. The adsorption purifier prepared in Preparation Example 3 was added to the filtrate at a dosage of 4 wt%. The mixture was stirred and adsorbed for 15 min. The adsorption purifier was separated by a magnet. After the filtrate met the standards, it was discharged.
[0064] Comparative Example 9 Compared with Example 3, the difference is that step (2) is not performed.
[0065] The details are as follows: (1) adjusting the pH value of the chemical nickel plating waste liquid to 7, then adding calcium chloride to the chemical nickel plating waste liquid, the amount of calcium chloride added is 13 g of calcium chloride per 100 mL of the chemical nickel plating waste liquid, stirring the reaction to precipitate for 1.5 hours, centrifuging, collecting the precipitate, and the precipitate is a substance containing calcium phosphate and calcium phosphite; (2) Carbon dioxide was introduced into the supernatant of step (1) at a ventilation rate of 75 mL / min for 1 h. The mixture was allowed to settle for 1 h. The adsorption purifier prepared in Preparation Example 3 was added to the filtrate at a dosage of 4 wt%. The mixture was stirred and adsorbed for 15 min. The adsorption purifier was separated by a magnet. After the filtrate met the standards, it was discharged.
[0066] Test Example 3 The discharged liquid and the original liquid in Examples 1-3 and Comparative Examples 1-9 were tested, and the results are shown in Table 3.
[0067] Table 3
[0068] It can be seen from the above table that after the treatment methods in Examples 1-3 of the present invention, the discharged liquid can meet the standard requirements and the nickel recovery rate is high.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid, characterized in that: The following steps are involved: (1) adjusting the pH value of the chemical nickel plating waste liquid, then adding calcium chloride to the chemical nickel plating waste liquid, stirring the reaction to precipitate, centrifuging, collecting the precipitate, and precipitating into a substance containing calcium phosphate and calcium phosphite; (2) adding sodium hydroxide to the supernatant in step (1) to adjust the pH value, centrifuging, separating the solid, adding hydrazine hydrate to the supernatant, stirring to react, and stopping adding hydrazine hydrate after no more bubbles are generated in the reaction solution, continuing to stir the reaction, standing to precipitate, centrifuging, and collecting the precipitate, which is a substance containing metallic nickel; (3) introducing carbon dioxide into the supernatant in step (2) to precipitate, adding an adsorption purifier to the filtrate, stirring and adsorbing, separating the adsorption purifier with a magnet, and discharging the filtrate after it meets the standards; The adsorption purifier is a material with magnetic ferroferric oxide as the core, loaded with doped TiO2 / ZnO, and then subjected to hydrogenation treatment, carbon nanotubes are deposited on the surface, and after being modified with polydopamine, the adsorption purifier is reacted with zirconium tetrachloride and 2-aminoterephthalic acid to obtain the adsorption purifier.
2. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 1, characterized in that: In step (1), the amount of calcium chloride added to the chemical nickel plating waste liquid is 12-15g of calcium chloride per 100mL of chemical nickel plating waste liquid, the stirring reaction precipitation time is 1-2h, and the pH value of the chemical nickel plating waste liquid is adjusted to 6.9-7.
1.
3. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 1, characterized in that: In step (2), the pH value is adjusted to 10-11, the stirring reaction time is 0.5-1h, and the stirring reaction time is continued for 0.5-1h.
4. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 1, characterized in that: In step (3), the amount of adsorption purifier added is 3-5wt%, the stirring adsorption time is 10-20min, the ventilation rate of carbon dioxide is 10-100mL / min, and the preparation method of the adsorption purifier is as follows: S1. Preparation of magnetic ferroferric oxide: under the protection of inert gas, ferric chloride and ferrous chloride are added to water, ammonia is added dropwise to adjust the pH value of the solution, heating and stirring the reaction, centrifuging, washing, ball milling, drying, and calcining to obtain magnetic ferroferric oxide; S2. Preparation of doped TiO2 / ZnO@magnetic ferroferric oxide composite: dissolve zinc acetate and cupric chloride in water, add diethylene glycol, and stir to form solution A; mix tetrabutyl titanate, thiourea, acetic acid and ethanol to obtain solution B; mix solution A and solution B, add magnetic ferroferric oxide, heat and stir to react, centrifuge, wash, ball mill, dry, and calcine to obtain doped TiO2 / ZnO@magnetic ferroferric oxide composite; S3. Hydrogenation treatment: The air was replaced by introducing an inert gas into the doped TiO2 / ZnO@magnetic ferroferric oxide composite, and then hydrogen was introduced, heated, the introduction of hydrogen was stopped, and cooled to room temperature to obtain a black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S4. Deposition of carbon nanotubes: dissolving ferrocene in xylene to obtain a solution, introducing an inert gas into the black doped TiO2 / ZnO@magnetic ferroferric oxide composite to replace the air, turning off the inert gas, introducing hydrogen, heating, adding the solution dropwise, then stopping heating and introducing hydrogen, cooling to room temperature, and obtaining a carbon nanotube-deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite; S5. Polydopamine modification: adding the prepared carbon nanotube deposited black doped TiO2 / ZnO@magnetic ferroferric oxide composite to water, adding dopamine hydrochloride and a catalyst, heating and stirring the reaction, separating with a magnet, washing, and drying to obtain a modified product; S6. Preparation of adsorption purifier: Add the modified substance, zirconium tetrachloride and 2-aminoterephthalic acid into N,N-dimethylformamide, stir and mix evenly, add acetic acid dropwise, perform hydrothermal reaction, separate by magnet, wash and dry to obtain adsorption purifier.
5. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 4, characterized in that: In step S1, the mass ratio of ferric chloride to ferrous chloride is 3.24:1.26, the pH value of the adjusted solution is 10-11, the temperature of the heated stirring reaction is 75-85°C, the time is 4-6h, and the calcination temperature is 400-600°C, the time is 1-3h.
6. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 4, characterized in that: The mass ratio of zinc acetate, cupric chloride, diethylene glycol, tetrabutyl titanate, thiourea, acetic acid and magnetic ferrosoferric oxide in step S2 is 7-10:0.2-0.4:3-5:12-15:1-2:4-6:6-8, the temperature of the heating and stirring reaction is 65-75°C, the time is 1-2h, and the calcination temperature is 500-600°C, and the time is 1-3h.
7. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 4, characterized in that: In step S3, hydrogen is introduced until the hydrogen pressure reaches 20-30 bar, and the temperature of the heating treatment is 180-220° C. for 4-6 days.
8. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 4, characterized in that: In step S4, the mass ratio of ferrocene to xylene is 1-2:100, the ventilation rate of hydrogen is 50-100 mL / min, and the heating temperature is 800-900°C.
9. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 4, characterized in that: In step S5, the mass ratio of the carbon nanotube deposited black doped TiO2 / ZnO@magnetic ferroferric oxide complex, dopamine hydrochloride and catalyst is 10:3-5:0.5-1, the catalyst has a pH of 8.5-9.5 Tris-HCl solution, the temperature of the heated and stirred reaction is 45-55°C, and the time is 3-5h.
10. The method for recycling nickel and phosphorus resources in chemical nickel plating waste liquid according to claim 4, characterized in that: In step S6, the mass ratio of the modified substance, zirconium tetrachloride, 2-aminoterephthalic acid and acetic acid is 10:4-5:3-4:2-4, the temperature of the hydrothermal reaction is 120-140° C., and the time is 20-24 hours.
Citation Information
Patent Citations
Nanometer material for ultraviolet light catalytic degradation and preparation method thereof
CN115739064A
Method for recycling iron phosphate from chemical nickel plating waste liquid
CN119191618A
Method for treating aged electroless nickel plating solution
JP2004131775A
Method for recycling electroless nickel plating waste solution
JP2005232517A
Magnetic chemical absorber, process for producing the same, method of regenerating the same, and method of treating waste liquid
WO2008023853A1